Mangled lower extremity: can we trust the amputation scores? - Fodor, Lucian (e-Century Publishing Corporation, 2012)
BACKGROUND: Limb injuries represent a constant and severe problem. Several lower limb injuries are more frequent than upper limb injuries. Over time, in an attempt to quantify the severity of traumas and to establish guidelines for the decision whether to save or amputate a mangled extremity, several scoring systems have been reported. Most refer to bone fractures, soft tissue damage, vascular, nerves and tendon lesions. MATHERIALS AND METHODS: Articles dealing with mangled lower extremities published in the last 15 years were analyzed. Other inclusion criteriaincluded:articles reporting MESS, PSI, LSI, and Gustillo-Anderson scores, studies based on groups of more than 25 patients, and English language articles. We tried to determine if there was good correlation between amputation recommendations and various scores of injury, with regard to combat wounds and civilian injuries, in adult and pediatric groups. RESULTS: Thirty-two papers fulfilled our criteria; in 17 of these, correlation between mangled extremity scores and the decision to amputate or salvage the limb was well-defined. Good correlation between MESS and amputation was found in 25% of the papers. The highest correlation was found for pediatric injuries and combined adult and pediatric combat injuries. CONCLUSIONS: The mangled extremity is a long-lasting, unsolved problem, with much debate and a large number of protocols and scoring systems, but with no unanimously-accepted solution. Many mangled extremities are borderline cases, and the decision to amputate or to salvage a limb must be carefully assessed. With advances in the medical field over the last 15 years, more mangled lower extremities are salvaged, especially in civilian injuries.